صعوبات تدريس المكفوفين من وجهة نظر المعلمين دراسة ميدانية بمدرسة ثامر المبروك للمكفوفين بالمسيلة - مليكة بن شعبان; اشراف: ميمون حدة (جامعة محمد بوضياف -المسيلة, 2025)
هدفت هذه الدراسة إلى التعرف على درجة وجود صعوبات في تدريس التلاميذ المكفوفين من وجهة نظر المعلمين. شمل مجتمع الدراسة جميع المعلمين الذين يزاولون عملهم بمدرسة الشهيد ثامر المبروك للمكفوفين بالمسيلة حيث تم تطبيق الدراسة على عينة بلغت 40 معلمًا ومعلمة، تمثلت في جميع معلمي المدرسة. ولتحقيق أهداف الدراسة، قامت الباحثة بإعداد استبيان تناول صعوبات تدريس التلاميذ المكفوفين وتكونت من 38 فقرة موزعة على أربع مجالات، وهي: الصعوبات المرتبطة بوضع الأهداف التعليمية، الصعوبات المرتبطة بالمناهج والكتب الدراسية، الصعوبات المرتبطة بالأساليب التدريسية والوسائل التعليمية، الصعوبات المرتبطة بالعملية التقييمية. لضمان صدق أداة الدراسة، تم استخدام صدق المحتوى، من خلال استطلاع آراء المحكمين. فحص الثبات بطريقة ألفا كرونباخ وتراوحت قيم معامل الاتساق الداخلي بين (0.81) و (0.92). استخدمت المتوسطات الحسابية والانحرافات المعيارية، واختبار (t-test)، ومعامل ارتباط بيرسون، وتحليل التبـاين الأحادي، كوسائل إحصائية لفحص فروض الدراسة، وأشارت النتائج إلى أن درجة وجود صعوبات في تدريس التلاميذ المكفوفين من وجهة نظر المعلمين كانت متوسطة، كما أكدت عدم وجود فروق ذات دلالة إحصائية في درجة وجود صعوبات في تدريس التلاميذ المكفوفين من وجهة نظر المعلمين. الكلمات المفتاحية: صعوبات تدريس، المكفوفين، المعلمين. Abstract: This study aimed to identify the degree of difficulties in teaching blind students from the teachers' point of view. The study population included all teachers working at the Martyr Thamer Al-Mabrouk School for the Blind in Messila, where the study was applied to a sample of 40 male and female teachers, representing all teachers of the school. To achieve the objectives of the study, the researcher prepared a questionnaire dealing with the difficulties of teaching blind students, consisting of 38 items distributed in four areas, namely: Difficulties related to setting educational goals, difficulties related to curricula and textbooks, difficulties related to teaching methods and teaching aids, and difficulties related to the evaluation process. To ensure the validity of the study instrument, content validity was used, through a survey of the judges' opinions. The internal consistency coefficient values ranged between (0.81) and (0.92). Arithmetic means, standard deviations, t-test, Pearson correlation coefficient, and univariate analysis of variance were used as statistical methods to test the hypotheses of the study, and the results indicated that the degree of difficulties in teaching blind students from the teachers ‘point of view was moderate, and confirmed that there were no statistically significant differences in the degree of difficulties in teaching blind students from the teachers’ point of view. Keywords: Teaching Difficulties, Blind, Teachers.